Factors contributing to Hypertension among Patients aged 18-45 years at Kajjansi Health Center IV, Wakiso District. A Cross-sectional Study. - Nambaziira, Dianah; Oluka, Julius (Student's Journal of Health Research Africa, 2022)
Background: Hypertension is the sustained increase in BP above normal measured on two occasions. It contributes to half of all global deaths due to NCDs and therefore the purpose of the study was to determine the factors contributing to hypertension among patients aged between 18-45 years at Kajjansi H/C IV Wakiso District. Methodology: A descriptive cross-sectional design was employed in carrying out this quantitative research. Kish and Leslie's method was used in determining the sample size of 50 respondents who were chosen by a simple random sampling technique. Results: Overall findings revealed that 54% of the hypertensive respondents were aged between 40-45 years of which 60% were females far more above their male counterparts who were at 40%, there was a positive correlation between hypertension and low intake of fruits and vegetables, physical inactivity and a positive family history to hypertension 50%,78%, and 66% respectively. Findings also showed that of the 54% of total respondents that had a normal body mass index, 58% had no chronic comorbidity while 18% of the remaining percentage had DM as comorbidity. The findings further revealed that nearly all the respondents (98%) were urban dwellers with a basic secondary education level of study (40%), and 50% were married. A strong relation between unemployment, smoking, and alcohol consumption with hypertension incidence was noted among respondents 66%, 72%, and 58% respectively. Conclusion: There is a positive correlation between hypertension and social factors that are more behavior-linked like cigarette smoking, alcohol intake, unemployment, and low fruit, and vegetable intake. Recommendation: The local authorities and village health teams to health educate the communities on how to protect themselves from hypertension.